Family support, learning environment, and life satisfaction among Chilean university students in a post-pandemic context: a mediation analysis - Zapata, Silvina Maria; Céspedes-Carreño, Cristian; Fuentealba-Urra, Sergio; Rosas-Maldonado, Maritza; Sánchez, Benjamín (Frontiers in Education, 2025)
IntroductionThe COVID-19 pandemic disrupted higher education globally, intensifying concerns over student wellbeing, especially in Latin America. This study explores how family support, academic engagement, and perceptions of the learning environment interact to influence life satisfaction among Chilean university students in a post-pandemic context, drawing on Bronfenbrenner's ecological systems theory.MethodsA cross-sectional survey was administered to 2,338 undergraduate students from a Chilean private university. Validated instruments measured family support, academic engagement and supportive academic climate, and life satisfaction. Mediation analyses were conducted using Hayes's PROCESS macro, with gender and age as covariates.ResultsFamily support was linked to life satisfaction in both direct and indirect ways, such as through university involvement and the quality of the learning environment. Mediation analyses showed a strong indirect path, which means that emotionally supportive home environments make students more interested in academics and make them feel like they are getting more help from the university, which makes them happier with their lives. The last model explained more than 32% of the differences in how happy people were with their lives.DiscussionThese results support an ecological view of wellbeing by showing how family (microsystemic) and academic (mesosystemic) aspects affect each other. This dual road highlights how crucial it is to design culturally relevant, all-encompassing programs that connect home and school settings in Latin America, where family ties usually continue strong until maturity.ConclusionImproving both family and institutional support networks may be very important for helping university students who have ongoing social and academic problems after the epidemic to be happier and more resilient.